Selective Lipolysis by Photoactivation of Chaperone-Mediated Autophagy Using Adipocyte Membrane-Coated Nanoparticle in Hydrogel - Choi, Jaehyun (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.